Semantic text extraction from CAPTCHA using Neural Networking - Chowdhury, Iftekhar Kabir; Jarif, Md. Nahiyan; Showmik, Sadman; Oishi, Farah Farhin; Bin Jinnat, Afif (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.